A MATHEMATICAL MODEL FOR MULTI-PERIOD SURGICAL SCHEDULING WITH CAPACITY CONSTRAINT - Wisittipanich, W.; Boonmee, C.; Khwanngern, K.; Chattinnawat, W.; Woschank, M. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
Surgical scheduling is a decision-making process that plays a crucial role in medical treatment. This research aimed to employ a mathematical programming model to solve the surgical scheduling problem. A mathematical model for a multi-period surgical scheduling problem with capacity constraints over a particular time horizon was proposed in this study. The goal was to schedule a list of patients who must undergo various kinds of operations. In particular, each operation of a patient must be performed during a specific time period by one of the eligible hospitals. In addition, each hospital has limited surgical capacity for each time period. The surgical scheduling problem was formulated with a multi-objective model using the weighted sum approach of two objectives: minimization of makespan and minimization of the total least preference assignment score. The experiment was executed using the simulated data according to the real treatments of cleft lip and cleft palate patients. The numerical results showed that the model yielded the optimal schedule which satisfied all constraints. The solution obtained from the model was similar to the current method. The proposed model also showed its superiority in terms of computational time and will be further used as a smart decision tool in the hospital scheduling.